Prenatal and Postnatal Manifestations of Congenital Chloride Diarrhea Due to a Heterozygote Variant of the SLC26A3 Gene: A Case Report - Cendal, Izabela; Szafrańska, Agnieszka; Fuchs, Tomasz; Patkowski, Dariusz; Smigiel, Robert; Królak-Olejnik, Barbara (Frontiers in Pediatrics, 2021)
Congenital chloride diarrhea (CCD) is caused by a recessive mutation in the SLC26A3 gene and characterized mainly by watery diarrhea, hypochloremia and metabolic alkalosis. Various different mutations in SLC26A3 are responsible for the disease. In the prenatal period, the symptoms of CCD may include polyhydramnios, preterm labor and abdominal distension. The main feature of CCD is chloride-rich diarrhea, which leads to excessive loss of fluid and salt immediately after birth and is followed by weight loss and dehydration. Hyponatremia and hypochloremia are soon accompanied by hypokalemia and metabolic alkalosis. Untreated CCD is fatal even in the first weeks of life. Diagnosis is made by high fecal chloride concentrations in patients with serum electrolytes corrected by salt substitution and confirmed using genetic testing of peripheral blood samples. Here, we detail prenatal and postnatal manifestations of a preterm infant, born via Caesarian section, who was suspected to suffer intrauterine bowel obstruction. Upper median laparotomy was performed and no intestinal abnormalities found. The course of the neonatal period was complicated by severe diarrhea with hypochloremia, hyponatremia and metabolic alkalosis. Based on the patient’s clinical picture and stool examination, a diagnosis of CCD was established. Mutation of the SLC26A3 gene was confirmed using genetic testing.